The rise of digital entrepreneurship: The strategic role of Third-Party Logistics (3PL) tech-driven platforms in scaling startups and e-commerce (Research, Society and Development, 2025)
The objective of the present study is to demonstrate that the rapid growth of digital entrepreneurship and e-commerce requires startups and small companies to find flexible and efficient logistics solutions capable of meeting consumers' increasing expectations for fast, traceable, and competitively priced deliveries. In this scenario, Third-Party Logistics (3PL) operators cease to act merely as operational service providers, becoming strategic partners driven by emerging technologies such as Artificial Intelligence, the Internet of Things (IoT), advanced WMS systems, and real-time integration platforms. This article investigates the fundamental role played by tech-driven 3PL platforms in the scaling process of digital businesses. The methodology adopts a systematic literature review and case analysis of Brazilian startups that utilize outsourced fulfillment models. It is concluded that the adoption of Logistics 4.0 solutions offers entrepreneurs decisive competitive advantages, such as variable costs, complete operational visibility, optimization of delivery time, and greater focus on the core business, constituting a strategic pillar for fast, sustainable, and data-driven growth.